Development of variable high frequency voltage source for ohmic heating process - Toudeshki, Arash Mohammadi (2010)
Heating is an important step in food processing. A new method of heating uses the natural electrical resistance of the food to generate heat. In this method electrical energy is transformed into thermal energy. This kind of food heating processing operation is called ohmic heating. The rate of ohmic heating critically depends on the electrical conductivity of the food during the process. Reviewing a number of researches shows that the usage of direct current for ohmic heating process causes electrolysis in liquid beverages. Moreover, usage of alternating current eliminates the probability of adverse electrochemical reaction. In addition, when the frequency increases, the risk of oxidation in electrodes will decrease. In this regard, for heating different kinds and sizes of food, it is necessary to have an electrical power source with variable output voltage and frequency. This research attempts to design, simulate and fabricate the variable frequency electrical power source to feed an ohmic heating process at high frequency (maximum 10 kHz). The three-phase resistive load is used and the experimental waveforms obtained are compared to simulation results. On the other hand, the total harmonic distortion in input current, power factor, efficiency and power losses of the fabricated system are investigated.